2015
DOI: 10.1111/ejh.12507
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a novel combination of two oral chelators deferasirox/deferiprone over deferoxamine/deferiprone in severely iron overloaded young beta thalassemia major patients

Abstract: Both iron chelation combination regimens were equally effective in reducing iron overload and improving QoL.DFP/DFX combination proved superior in improving cardiac T2*, treatment compliance, and patients satisfaction with no greater adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 35 publications
4
80
2
Order By: Relevance
“…Many subsequent publications have reported that in comparison with DFO monotherapy, combination therapy and DFX monotherapy have more significant effects on iron overload and myocardial improvement [31, 32]. These findings were similar to recently published data [33] showing that DFP/DFX combination is superior in improving cardiac T2*. Each of these therapies has advantages and shortcomings, and tailoring therapy to individual patients is important for optimizing treatment outcome.…”
Section: Discussionsupporting
confidence: 82%
“…Many subsequent publications have reported that in comparison with DFO monotherapy, combination therapy and DFX monotherapy have more significant effects on iron overload and myocardial improvement [31, 32]. These findings were similar to recently published data [33] showing that DFP/DFX combination is superior in improving cardiac T2*. Each of these therapies has advantages and shortcomings, and tailoring therapy to individual patients is important for optimizing treatment outcome.…”
Section: Discussionsupporting
confidence: 82%
“…Combination of oral chelators DFP and DFX, offers the advantage of improved compliance as compared to DFO. The hypothesis is that the administration of thrice daily DFP and once daily DFX, will ensure exposure to chelating agents and suppression of toxic iron species at all times, thus limiting end organ damage [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…The oral combination of DFP and DFX is a potentially attractive option in heavily iron overload patients, particularly in those with a suboptimal response to monotherapy. A recent randomized trial, few case reports and small series have successfully evaluated this combination [4][5][6][7][8]. The purpose of the study was to prospectively record adverse events, including hepatic, renal, and hematological parameters, and to assess iron overload by serial measurement of serum ferritin over a period of 1 year in patients with bthalassemia major on dual oral iron chelators.…”
mentioning
confidence: 99%
“…The results of our study disagree with their results. 22 Xia et al in a meta-analysis showed that in comparing DFX with DFO, a significant difference was shown on SF level (P=0.003), and there was no difference between DFX and DFO in safety evaluation. The results of this study were similar to our results.…”
Section: -11mentioning
confidence: 99%